Against the tide : Rickover's leadership principles and the rise of the nuclear Navy - Oliver, Dave, 1941- (Naval Institute Press, 2014)
"Drawn from a wealth of untold stories, Against the Tide is a leadership book that illustrates how Adm. Hyman Rickover was the innovative driving force behind America's nuclear submarine navy and how he revolutionized naval warfare in the latter half of the twentieth century. Rickover's single-minded focus on safety protected Americans from nuclear contamination, a record that contrasts with the dozens of nuclear reactor accidents suffered by the Russians. While Rickover has been the subject of numerous biographies, little has been written about his unique management practices; however, Dave Oliver had the good fortune to know and to serve under Rickover during much of his thirty-year career in the Navy and is singularly qualified to explain the management and leadership principles behind Rickover's success"--